KERJASAMA AMERIKA SERIKAT – FILIPINA DALAM PERANG MELAWAN TERORISME DI FILIPINA - Irfan Nurhakim (Global Political Studies Journal, 2017)
This study discusses the cooperation between the United States and the Philippines in war on terrorism in the Philippines that began from 2001 until 2014. The United States helps the Philippines in war on terrorism because of the Al-Qaeda connection as the perpetator behind 9/11 event with groups in the Philippines such as the Abu Sayyaf Group, MILF and Jamaah Islamiyah. This study uses data collection techniques through literature study because the data obtained comes from articles/magazines/internet/documents. Data analysis techniques using data reduction techniques so data that has been obtained from the article/magazine/internet/documents are reducted to be taken an important point. Based on the results obtained from 2001-2014, the strength of the Abu Sayyaf Group is reduced and has successfully overcome the conditions under which terrorism is born so that this cooperation can be said to succeed